Tanggung Jawab Perdata Influencer terhadap Klaim Produk dalam Endorsement: Tinjauan Hukum Atas Perlindungan Konsumen Berdasarkan UU No. 8 Tahun 1999 dan Perkembangan Praktik Digital di Indonesia - Gunawan Widjaja; Songga Aurora Abadi; Yuri Anggi (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
The advancement of digital technology has introduced a novel trend in marketing via social media platforms, specifically through influencers promoting products or services. Nonetheless, numerous endorsements by influencers contain misleading, inaccurate, or harmful claims to consumers. This research aims to analyze the civil liability of influencers for product claims that cause consumer harm in digital media endorsements, referencing Law No. 8 of 1999 on Consumer Protection. Utilizing a normative juridical method based on literature review of laws, legal doctrines, and pertinent cases, the findings reveal that influencers can be held civilly liable under the tort principle (onrechtmatige daad) as stipulated in Article 1365 of the Civil Code, if proven to provide false or unsupported claims resulting in consumer harm (Setiawan, 2019). Therefore, there is a pressing need to enhance regulations governing the role of influencers in consumer protection frameworks alongside effective liability mechanisms as a form of accountability in the evolving digital marketing landscape.